Protocol for detection of tRNA-derived fragments in cells, tissues, and plasma - Mengqian Yu; Pengyuan Liu; Yan Lu (STAR Protocols)
Summary: tRNA-derived fragments (tRFs) are frequently dysregulated in cancers, and approaches for the detection of tRFs within biological samples are vital for their expression analysis and functional exploration. Here, we present a protocol for detecting tRFs using a modified TaqMan quantitative real-time PCR (qRT-PCR)-based technique, Dumbbell-PCR (Db-PCR). We describe steps for primer and adapter design, adapter-RNA ligation, and RNA detection. This protocol streamlines and enhances the precision of tRF quantification in cells, tissues, and plasma, facilitating a time-efficient and reliable assessment of their presence.For complete details on the use and execution of this protocol, please refer to Yu et al.1 and Sun et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.